Human body exergy consumption models' evaluation and their sensitivities towards different environmental conditions. (15th September 2019) - Guo, Hongshan; Luo, Yongqiang; Meggers, Forrest; Simonetti, Marco
Abstract: We can use the concept of exergy to analyze a human body as a heat emitter: while generating heat continuously, the body remains at roughly the same temperature through physiological responses such as shivering, sweating, breathing thus raising/decreasing the core and/or skin temperature to maintain effective heat dissipation. Existing literature provides an estimated exergy consumption rate of the human body ranging from 2 to 5 W / m 2, while nearly unanimously agreeing on a local exergy consumption minima points to potential individual thermal comfort. To clarify the underlying assumptions used in the existing human body exergy models, we analytically and numerically reviewed the terms used for assessing metabolism, radiation, evaporation, and convection exergy changes of the human body in this paper. We observed overestimations of exergy from metabolism, underestimations of exergy change through radiation, and some caveats in the signage of convective exergy losses in the results we obtained. We were also able to propose an improved expression to estimate human body radiation exergy exchanges as well as selecting reference temperatures that are more process-specific. Future studies that provide experimental verification of these models were also deemed necessary. Highlights: Term-by-term comparison of existing human body exergy model expressions; Showed T op/E cons minima combination for male/female occupants across age span; Compared linear radiant heat transfer coefficient against actual radiation heat transfer; Showed how reference temperature affects the sign of evaporation exergy loss.